Deoxygenation in anisole decomposition over bimetallic catalysts supported on HZSM-5 - Zhang, Jiajun; Fidalgo, Beatriz; Wagland, Stuart T.; Shen, Dekui; Zhang, Xiaolei; Gu, Sai (Elsevier, 2018)
This work investigated the deoxygenation reaction in anisole decomposition over HZSM-5 (HZ(25)) zeolite supported bimetallic catalysts to produce benzene, toluene and xylene (BTX). Experiments were performed in order to evaluate the synergistic effect between the two active metals with the focus on the effect of temperature, metal type, and metal loading ratio. Experimental results showed that 1%Ni-1%Mo/HZ(25) led to both the highest BTX yield (i.e. 30.0 wt%) and selectivity (i.e. 83.7%). On the contrary, bimetallic catalysts containing Fe were less effective in promoting the BTX production. It was identified that the optimum temperature for BTX production over 1%Ni-1%Mo/HZ(25) catalysts was 500 °C. Characterization of fresh and spent catalysts showed microcrystal particles of bi-metal loadings highly dispersed on the zeolite surface, and some agglomeration of metallic particles were also observed. Large amount of carbonaceous deposit was observed on the spent catalysts mainly in the form of amorphous. Density Functional Theory (DFT) modelling was carried out in order to study the adsorption energy of anisole and phenol molecules onto Ni-Mo, Ni-Fe and Mo-Fe surfaces; and the interactions between phenol molecule and bimetal surfaces were further analysed. All the analysed bimetal surfaces exhibited strong interactions with the adsorbed molecule. Ni-Mo surface declined electrons energy levels mainly around 1.5 eV in the adsorbate molecule and released the highest adsorption energy; while Ni-Fe and Mo-Fe surface led to more electrons exchange with the adsorbate during the adsorption. The modelling results agreed well with experiments by revealing that the strong binding between phenolic compounds (Phs) and the Ni-Mo based catalysts bimetal surface would lead to a higher BTX production in the deoxygenation reaction in the decomposition of anisole.
Keywords: Lignin; Catalytic decomposition; Deoxygenation; Anisole; Bimetallic supported catalyst; Phenolic compounds